2001
DOI: 10.1186/1471-2091-2-7
|View full text |Cite
|
Sign up to set email alerts
|

The fission yeast COP9/signalosome is involved in cullin modification by ubiquitin-related Ned8p

Abstract: Background The function of the fission yeast cullins Pcu1p and Pcu4p requires modification by the ubiquitin-related peptide Ned8p. A recent report by Lyapina et al. shows that the COP9/signalosome (CSN), a multifunctional eight subunit complex, regulates Ned8p modification of Pcu1p. Disruption of caa1/csn1 , which encodes subunit 1 of the putative S. pombe CSN, results in accumulation of Pcu1p exclusively in the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Nedd8 is a small ubiquitin-like protein that is conjugated to the K720 residue of Cul-1 (and to an homologous lysine in all other Cullins as well) using Uba3 (E1), Ubc12 (E2), and Roc1 (E3) [28] , [29] , [30] , [31] . This modification is in turn cleaved off by the multi-subunit COP9 Signalosome (CSN) [32] , [33] . Since mutations in the pathways that conjugate and remove Nedd8 are detrimental, the current model is that cycles of neddylation and de-neddylation are necessary for the proper function of CDL [34] , [35] , [36] .…”
Section: Resultsmentioning
confidence: 99%
“…Nedd8 is a small ubiquitin-like protein that is conjugated to the K720 residue of Cul-1 (and to an homologous lysine in all other Cullins as well) using Uba3 (E1), Ubc12 (E2), and Roc1 (E3) [28] , [29] , [30] , [31] . This modification is in turn cleaved off by the multi-subunit COP9 Signalosome (CSN) [32] , [33] . Since mutations in the pathways that conjugate and remove Nedd8 are detrimental, the current model is that cycles of neddylation and de-neddylation are necessary for the proper function of CDL [34] , [35] , [36] .…”
Section: Resultsmentioning
confidence: 99%
“…The COP9 signalosome (CSN), a conserved eight-protein complex, is a major regulator of the Cullin-RING-based ubiquitin ligases [25] , [26] , [27] . CSN controls Cullin-based ubiquitin ligases by removing the Nedd8 modification from the Cullin component of the ligase [28] , [29] , [30] , [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in function of different CSN subunits leads to different phenotypes which may indicate that each CSN subunits has unique roles [4,5,27]. Thus, CSN’s function can be regulated by engineering particular subunits [28]. The following sections review data available for the reported hypomorphic mutants of CSN subunits.…”
Section: Characteristics Of Csn Hypomorphic Mutants and Their Impomentioning
confidence: 99%